Structural basis for human TRPC5 channel inhibition by two distinct inhibitors - Song, Kangcheng (eLife, 2021)
TRPC5 channel is a nonselective cation channel that participates in diverse physiological processes. TRPC5 inhibitors show promise in the treatment of anxiety disorder, depression, and kidney disease. However, the binding sites and inhibitory mechanism of TRPC5 inhibitors remain elusive. Here, we present the cryo-EM structures of human TRPC5 in complex with two distinct inhibitors, namely clemizole and HC-070, to the resolution of 2.7 Å. The structures reveal that clemizole binds inside the voltage sensor-like domain of each subunit. In contrast, HC-070 is wedged between adjacent subunits and replaces the glycerol group of a putative diacylglycerol molecule near the extracellular side. Moreover, we found mutations in the inhibitor binding pockets altered the potency of inhibitors. These structures suggest that both clemizole and HC-070 exert the inhibitory functions by stabilizing the ion channel in a nonconductive closed state. These results pave the way for further design and optimization of inhibitors targeting human TRPC5.